STRATEGIC FINANCIAL MANAGEMENT: THE IMPACT OF COST ANALYSIS AND OPERATIONAL EFFICIENCY ON PROFITABILITY - Hoog, Barbara Andrade Ferraz Martins (Revista Sistemática, 2022)
This article discusses the critical role of strategic financial management in enhancing organizational profitability through rigorous cost analysis and operational efficiency. It examines how financial control tools and budgeting practices optimize resource allocation and reduce inefficiencies, fostering sustainable growth. The integration of advanced digital technologies enables real-time financial insights and adaptive planning, essential for navigating market volatility and fostering innovation. By promoting a culture of financial discipline and accountability, strategic financial management supports improved performance and long-term viability in competitive environments.